Heating and emission characteristics from combustion of charcoal and co-combustion of charcoal with faecal char-sawdust char briquettes in a ceramic cook stove. Issue 8 (August 2022) - Otieno, Austine O.; Home, Patrick G.; Raude, James M.; Murunga, Sylvia I.; Gachanja, Anthony
Abstract: Over reliance on charcoal has accelerated deforestation in sub-Saharan Africa. Seeking alternative sustainable and environmentally friendly sources of biomass energy to meet the escalating energy demand is therefore vital. However, limited evidence exists on the concentrations of toxic emissions of different biomass fuels. Herein, dried human faeces and sawdust were pyrolyzed at 350 °C to produce biochar and mixed in equal ratio to produce briquettes through densification, with molasses (10 wt.%) used as a binder. A comparative study on the heating properties and emission level of carbon monoxide (CO), nitric oxide (NO), and hydrogen sulphide (H2 S) during combustion of charcoal, and co-combustion (50:50 wt. %) of charcoal with briquettes was conducted. The thermal profile of the flue gases indicated rapid combustion of volatile gases followed by slow oxidation of the char. Co-combustion significantly (P < 0.05) enhanced the amount of heat energy released with flue gases temperatures reaching a peak of 475 °C. The briquettes had a gross calorific value of 19.8 MJ/kg which was lower than 25.7 MJ/kg for charcoal. Combustion of charcoal did not emit NO, however the concentration of CO was above the critical short term limits of 35 ppm. The concentration of CO and H2 S was above the short term exposure limits of 35 ppm, and 0.005 ppm, respectively, during co-combustion, whereas NO concentration was below dangerous exposure levels of 100 ppm. These results suggest that co-combustion of charcoal with the briquettes is a promising approach to generate safe and sufficient heat energy for cooking and reduce deforestation. Abstract : Biomass; Bioenergy; Calorific values; Exposure limits; Flue gases; Indoor heating.